Aprendizagem baseada em equipes: uma intervenção educacional promovendo competências em cuidados paliativos - Oliveira, Talitha Tonini de (2021)
In Brazil, there are few structured services, trained professionals or holders of the principles of Palliative Care. The knowledge gap on the subject becomes an obstacle for the development of the area. The National Curriculum Guidelines for the Medicine course advocate the formation of a more ethical and humanistic professional and include the confrontation of the death process in medical education, for this, they adopt the Active Methodology to change this scenario. The study aims to: carry out an educational intervention on palliative care with 6th-year medical students and medical residents, using the Team-Based Learning (TBL) strategy, evaluate the self-perception of palliative care skills of the participants before and after the intervention, evaluate the educational intervention. It is descriptive, analytical, transversal, quantitative and qualitative research of educational intervention. The sample consisted of 13 students from the 12th period of the Medicine course at UNIFEV and 8 residents of the Medical Clinic of Santa Casa de Votuporanga. The intervention followed the steps of the adopted strategy: pre-class preparation, guarantee of preparation, application of concepts. A diagnostic evaluation was carried out before and after the educational intervention through a self-administered questionnaire, the instrument used was: Likert-type instrument for the Assessment of Self-Perception of Skills Development in Palliative Care in Family and Community Medicine1, which addresses the themes: communication in care palliative care, increased comfort in illness including terminal phase, emergency palliative care, end-of-life care. The intervention was qualitatively evaluated through the participants' opinions and quantitatively through descriptive statistics with the creation of contingency tables of absolute and relative frequency. The results of the pre- and post-test evaluations showed a significant improvement in the participants' self-perception regarding the analyzed competences. The inference means for the comparison of competences between pre- and post-tests showed significant differences, considering p<0.05. The one with the greatest evolution was competence in communication (1.029, p=0.0001) and the one with the lowest evolution was competence in emergencies (0.865, p=0.0001). According to the participants, the intervention improved the level of knowledge in Palliative Care, which was previously shallow and insufficient; allowing correction of previous concepts and ideas through immediate feedback. The group discussion and the applicability of the theme were stimulating and strong points of the intervention; the lack of individual preparation and dysfunctional competitiveness among the participants were the greatest difficulties encountered, added to the prolonged time of the activity. TBL proved to be an adequate intervention, improving participants' perception of palliative care and attitudes in clinical practice. The great need to encourage continuous learning is reinforced, as well as to work more deeply on Palliative Care in graduation.